Linking Microbial Enzymatic Activities and Functional Diversity of Soil around Earthworm Burrows and Casts - Lipiec, Jerzy; Frąc, Magdalena; Brzezińska, Małgorzata; Turski, Marcin; Oszust, Karolina (Frontiers in Microbiology, 2016)
The aim of this work was to evaluate the effect of earthworms (Lumbricidae) on the enzymatic activity and microbial functional diversity in the burrow system (burrow wall 0–3 mm, transitional zone 3–7 mm, bulk soil >20 mm from the burrow wall) and cast aggregates of a loess soil under a pear orchard. The dehydrogenase, β-glucosidase, protease, alkaline phosphomonoesterase, and acid phosphomonoesterase enzymes were assessed using standard methods. The functional diversity (catabolic potential) was assessed using the Average Well Color Development and Richness Index following the community level physiological profiling from Biolog Eco Plates. All measurements were done using soil from each compartment immediately after in situ sampling in spring. The enzymatic activites including dehydrogenase, protease, β-glucosidase and alkaline phosphomonoesterase were appreciably greater in the burrow wall or casts than in bulk soil and transitional zone. Conversely, acid phosphomonoesterase had the largest value in the bulk soil. Average Well Color Development in both the transitional zone and the bulk soil (0.98-0.94 A590nm) were more than eight times higher than in the burrow walls and casts. The lowest richness index in the bulk soil (15 utilized substrates) increased by 86-113% in all the other compartments. The PC1 in principal component analysis (PCA) mainly differentiated the burrow walls and the transitional zone. Utilization of all substrate categories was the lowest in the bulk soil. The PC2 differentiated the casts from the other compartments. The enhanced activity of a majority of the enzymes and increased microbial functional diversity in most earthworm-influenced compartments make the soils less vulnerable to degradation and thus increases the stability of ecologically relevant processes in the orchard ecosystem.